1990
DOI: 10.1042/bj2710473
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin is a candidate for a calsequestrin-like function in Ca2+-storage compartments (calciosomes) of liver and brain

Abstract: In a search for the non-muscle equivalent of calsequestrin (the low-affinity high-capacity Ca2(+)-binding protein responsible for Ca2+ storage within the terminal cisternae of the sarcoplasmic reticulum), acidic proteins were extracted from rat liver and brain microsomal preparations and purified by column chromatography. No calsequestrin was observed in these extracts, but the N-terminal amino acid sequence of the major Ca2(+)-binding protein of the liver microsomal fraction was determined and found to corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 41 publications
1
69
2
Order By: Relevance
“…This protein has an apparent molecular mass of 60 kDa on SDS-PAGE, and a molecular mass of 46 kDa has been established by molecular cloning [3,4]. Calreticulin is found mainly in the ER [3] and in vesicles called calciosomes ( [2], see [5] as a review). Its function remains unclear although a role in calcium sequestration has been proposed.…”
Section: Calrcticulinmentioning
confidence: 99%
“…This protein has an apparent molecular mass of 60 kDa on SDS-PAGE, and a molecular mass of 46 kDa has been established by molecular cloning [3,4]. Calreticulin is found mainly in the ER [3] and in vesicles called calciosomes ( [2], see [5] as a review). Its function remains unclear although a role in calcium sequestration has been proposed.…”
Section: Calrcticulinmentioning
confidence: 99%
“…However MacLennan and coworkers, who first described calreticulin [223], had already reported its capacity to bind more than 20 mol Ca2+/mol protein with low affinity. We have recently characterized calreticulin from rat liver and observed that (in addition to the high-affinity site) it also binds up to 50 mol Ca2+/mol protein with low affinity, (Kd = 1 mM) [299]. Calreticulin cross-reacts with a few anti-(skeletal muscle calsequestrin) antibodies, particularly in its native form [299].…”
Section: Cu2+ Bujjering Within Non-muscle Stores Calreticulinmentioning
confidence: 99%
“…We have recently characterized calreticulin from rat liver and observed that (in addition to the high-affinity site) it also binds up to 50 mol Ca2+/mol protein with low affinity, (Kd = 1 mM) [299]. Calreticulin cross-reacts with a few anti-(skeletal muscle calsequestrin) antibodies, particularly in its native form [299]. In ultrathin cryosections, anti-calreticulin antibodies, coated with gold particles, localize in vesicular structures which are morphologically indistinguishable from calciosomes [299].…”
Section: Cu2+ Bujjering Within Non-muscle Stores Calreticulinmentioning
confidence: 99%
See 1 more Smart Citation
“…It also acts as a classical chaperone for nonglycosylated proteins by preventing protein aggregation in an in vitro model (22). CRT is an important regulator of Ca 2ϩ homeostasis within the ER (23,24). Total CRT expression is up-regulated by many forms of cellular stress, including amino acid deprivation, depletion of Ca 2ϩ stores, oxidative stress, and hypoxia (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%